2009
DOI: 10.1016/j.jacc.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Cost-Effectiveness of Coronary Computed Tomography Angiography in the Evaluation of Patients With Chest Pain

Abstract: CCTA is comparable to other diagnostic studies and might hold good clinical value, but large randomized controlled trials are needed to guide policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 70 publications
2
52
0
1
Order By: Relevance
“…Several other studies have also concluded that little differences in health outcomes across diagnostic strategies exist [25][26][27]. Furthermore, it was concluded that coronary CT angiography can be a cost-saving technique [26][27][28] that can help to avoid unnecessary invasive angiograms [27], although these results were found in studies evaluating the cost-effectiveness of 64-slice CT which has lower accuracy estimates than NGCCT.…”
Section: Scenario Analysesmentioning
confidence: 99%
“…Several other studies have also concluded that little differences in health outcomes across diagnostic strategies exist [25][26][27]. Furthermore, it was concluded that coronary CT angiography can be a cost-saving technique [26][27][28] that can help to avoid unnecessary invasive angiograms [27], although these results were found in studies evaluating the cost-effectiveness of 64-slice CT which has lower accuracy estimates than NGCCT.…”
Section: Scenario Analysesmentioning
confidence: 99%
“…33 When stress MPI was replaced with coronary CTA, at a coronary CTA cost of $420 and sensitivity and specificity of 92% and 79%, respectively, GES yielded health plan savings, with PMPM savings of $0.29 at a 50% GES capture rate. 8,18,37,38 At 100% capture rate, PMPM savings increased to $0.57.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The model was implemented in Microsoft Excel 2011 (Microsoft Corporation, Redmond, WA); the study team previously developed decision analysis models using this software to perform economic evaluations of health care interventions. [18][19][20] All costs were assessed from a commercial payer's perspective in 2012 US dollars. One-way sensitivity analyses were conducted on all model parameters by varying each parameter across its range and assessing the impact on results.…”
Section: Overview and Model Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A recent decision analytic model examined a comparison of the cost-effectiveness of CCTA to MPS in stable chest pain patients, specifically modeling out the costs of incidental findings and nondiagnostic examinations [19]. The authors of this analysis determined that health outcomes of individuals undergoing CCTA or MPS were similar, but with small gains in quality-adjusted life years (QALY) conferred by undergoing CCTA.…”
Section: Resource Utilization Costs and Clinical Outcomesmentioning
confidence: 99%